Enhancing Disability Inclusion in Higher Education: Merilee Grindle Model Perspective in Policy Implementation for Achieving Sustainable Development Goal 16 - Anggalini, Titis Dewi; Febriani, Alfiana; Kurnianingtyas, Rida; Naila, Aulia Sulfiannur; Widyastuti, Risqi; Wulanningsih, Fitri (Yogyakarta State University, 2024)
Inclusiveness policies in services, including education, are an important mandate, especially related to access for people with disabilities. This study focuses on universities as education service providers, which are committed to improving supporting facilities for lectures for people with disabilities. The objectives of the study include: (1) the influence of disability facility policies on achieving SDG's 16, (2) efforts by universities to fulfill the policy mandate, and (3) challenges and opportunities for its implementation. Using the Merilee Grindle model, this study highlights the implementation of policies related to SDG's 16, namely Peace, Justice, and Strong Institutions. The Mix Methods method with a sequential explanatory approach is used. In the first stage, quantitative analysis was carried out with a simple linear regression test, followed by qualitative data collection using the Miles and Huberman interactive model. The results show that the implementation of disability facility policies has a significant impact on achieving SDG's 16. Universities have shown commitment through the provision of disability-friendly infrastructure, supportive regulations, and mentoring and training programs. The main opportunity is the commitment of university leaders to disability inclusion. However, major challenges remain, especially in the suboptimal policy monitoring and evaluation system.